A systematic replication of teaching children with autism to respond appropriately to lures from strangers. Issue 4 (19th October 2014) - Bergstrom, Ryan; Najdowski, Adel C.; Tarbox, Jonathan
<x xml:space="preserve">Abstract</x> We evaluated the effects of behavioral skills training in the home for teaching children with autism to abstain from going with strangers and immediately inform a familiar adult of the stranger's attempt to lure them in the natural environment. All participants learned to respond correctly to lures in the home and demonstrated concomitant changes in untrained natural settings. In situ training and an added incentive were necessary for 1 participant.